2006
DOI: 10.1007/s00244-005-0186-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Phosphate on the Response of Periphyton to Atrazine Exposure

Abstract: After indications from the literature that nutrient concentrations may modify the toxicity of herbicides to natural periphyton communities, this study aims to provide experimental proof for atrazine. In this microcosm experiment, phosphate (P) addition did not ameliorate atrazine toxicity to periphyton. Three weeks of P addition did not increase atrazine tolerance (measured as EC50 in acute toxicity tests), whereas exposure to atrazine under conditions that were either P-limited or non-P-limited clearly reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
27
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 27 publications
2
27
0
Order By: Relevance
“…The genetically stable populations of microbes in a biofilm generate varied sensitivities and responses to various anthropogenic pressures (Mcclellan et al 2008). PO 4 3-ions particularly influence the sensitivity of bacterial community in biofilm for toxicants (Kamaya et al 2004;Guasch et al 2007;Tlili et al 2010). Additionally, Tlili et al (2010) demonstrated the shift in the microbial community in response to toxicants such as Cu and diuran (herbicide), especially in conditions of nutrient deficiency.…”
Section: Microbial Assemblage (Biofilm) and Its Role In Aquatic Ecosymentioning
confidence: 99%
See 1 more Smart Citation
“…The genetically stable populations of microbes in a biofilm generate varied sensitivities and responses to various anthropogenic pressures (Mcclellan et al 2008). PO 4 3-ions particularly influence the sensitivity of bacterial community in biofilm for toxicants (Kamaya et al 2004;Guasch et al 2007;Tlili et al 2010). Additionally, Tlili et al (2010) demonstrated the shift in the microbial community in response to toxicants such as Cu and diuran (herbicide), especially in conditions of nutrient deficiency.…”
Section: Microbial Assemblage (Biofilm) and Its Role In Aquatic Ecosymentioning
confidence: 99%
“…The increased number of bacteria cause odor and taste problems in the freshwaters (Okabe et al 2002). Aquatic plant-associated biofilm is capable to degrade the algal-derived organics containing chiefly amines, aliphatic aldehydes and phenolics (Simpson 2009) and dissolved organic matter (DOM) (Tranvik 1998) such as PCBs (poly-chlorinated biphenyls) (Ghosh et al 1999) and atrazine (Guasch et al 2007). Additionally, rhizoplane of aquatic plants are also rich in ubiquitous methanotrophs a group of a and c proteobacteria, utilizing methane for energy and as carbon source (Semrau et al 2010).…”
Section: Degradation Of Organic Pollutantsmentioning
confidence: 99%
“…Several authors have previously reported increased community tolerance to Irgarol in freshwater communities (8,79) and to other PS II inhibitors in both freshwater (23,40,70,92) and marine (7,80,96) communities. It should be noted, however, that the magnitudes of the PICT responses were quite small in some of these studies.…”
mentioning
confidence: 99%
“…These inhibitors replace the native plastoquinone at the Q B -binding niche in the D1 protein within PS II (29,72,86,105). This results in various toxic effects like inhibition of photosynthetic electron transport, which in turn leads to reduced ATP and NADPH production (25, 29) and oxidative stress due to the accumulation of reactive oxygen species (ROS) at PS II (29,31,85,89,91).Several authors have previously reported increased community tolerance to Irgarol in freshwater communities (8,79) and to other PS II inhibitors in both freshwater (23,40,70,92) and marine (7,80,96) communities. It should be noted, however, that the magnitudes of the PICT responses were quite small in some of these studies.…”
mentioning
confidence: 99%
“…However, the pesticide contamination of fresh water is causing concern with respect to long-term and low-dose effects of pesticides on the public health, as well as to their impact on non-target species. Thus, intensive research on the fate of pesticides in the environment is needed (Sudo et al, 2002;Guasch et al, 2007).…”
mentioning
confidence: 99%